Pendidikan Anti Korupsi untuk Siswa Sekolah Menengah Pertama - Setyo Pamungkas; Selvie Novitasari; Sri Harini Dwiyatmi; Yonathan Imananta; Marsela Dorthea Maabuat (Jurnal Hukum Lex Generalis, 2024)
The purpose of this community service is to disseminate anti-corruption to the younger generation-students through anti-corruption education. This activity was carried out because of the fact that information about anti-corruption is still low among the younger generation. The method used is using Anti-Corruption Education game props. The two main materials in this activity are material about corruption, corrupt behavior and anti-corruptionbehavior and games. Anti-Corruption Education uses props as the second main material. Games using these props are an implementation of knowledge and understanding about corruption, corrupt behavior & anti-corruption behavior. On average, students participating in this education have only participated in anti-corruption education once. This education is able to provide knowledge and understanding about corruption, corrupt behavior and anti-corruption behavior to students. There is an increase in understanding of corruption, corrupt behavior and anti-corruption behavior. This can be seen in the results of the pre-test and post-test that were made. In the post-test, students can understand and identify various types of corruption, forms of corrupt behavior and forms of anti-corruption behavior that were previously unknown.